2017
DOI: 10.1007/s00284-017-1252-8
|View full text |Cite
|
Sign up to set email alerts
|

Expression Changes in Metal-Resistance Genes in Microbacterium liquefaciens Under Nickel and Vanadium Exposure

Abstract: Microbacterium liquefaciens MNSH2-PHGII-2 is a nickel-vanadium-resistant bacterium isolated from mine tailings located in Guanajuato, Mexico. In PHGII liquid media, M. liquefaciens has the ability to remove 29.5 ppm of Ni and 168.3 ppm of V. The present study reports, for the first time in M. liquefaciens, the presence of the genes nccA (Ni-Co-Cd resistance), hant (high-affinity nickel transporter), smtA, a metal-binding protein gene, and VAN2 (V resistance), which showed an increased expression under exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 51 publications
0
5
0
1
Order By: Relevance
“…A detailed study revealed the effects of nickel and vanadium uptake by M. liquefaciens. [3] Nickel and vanadium at low concentrations are indispensable for several bacterial cellular processes, but higher concentrations of nickel and vanadium introduce cytotoxicity. [53] The resistance mechanisms to metal excesses in bacteria include bioaccumulation, ion internalization/ externalization and biosorption.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A detailed study revealed the effects of nickel and vanadium uptake by M. liquefaciens. [3] Nickel and vanadium at low concentrations are indispensable for several bacterial cellular processes, but higher concentrations of nickel and vanadium introduce cytotoxicity. [53] The resistance mechanisms to metal excesses in bacteria include bioaccumulation, ion internalization/ externalization and biosorption.…”
Section: Discussionmentioning
confidence: 99%
“…[53] The genetic mechanisms that regulate the genetic expression pathways are not well understood, but the overexpression of these genes in response to nickel and vanadium are important for their metabolism in M. liquefaciens allowing for bacterial survival. [3] Nickel and vanadium were reported to enter the cell via several transporters, e. g. nccA, hant, and VAN2 before incorporating these metal ions into enzymes, metalloproteins and storage reservoirs and interacting reversibly with metalloregulators. [54][55][56][57][58]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…145 In another aspect, intracellular reactive oxygen species (ROS) are generated during V(V) bioreduction, 146 doing harm to microbes, which triggers a detoxification process by ROSscavenging enzymes such as superoxide dismutase and catalase. 130 Additionally, V-resistance genes were gradually discovered, such as van2, czcD, cnrB2, and smtAB, 147,148 which help microorganisms survive in V-existing environments. Microbial catalysis can improve the V(V)-reduction efficacy of a substance.…”
Section: T H Imentioning
confidence: 99%
“…Asimismo, este elemento es altamente valorado por la industria de la fabricación de aleaciones (con Fe, Cu, Cr y Zn) por lo que la minería del Ni aporta residuos principalmente por la extracción y beneficio de minerales de pentlandita (Ni,Fe)9S8, millerita (NiS), NiSb, NiAs2, NiAsS, NiSbS y garnierita (Si4O13[Ni, Mg]2•2 H2O) [28], [54]. [87].…”
Section: Ni (Níquel)unclassified